2015
DOI: 10.1097/aog.0000000000001042
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of 12-Hour Urine Collection for the Diagnosis of Preeclampsia

Abstract: A 12-hour urine collection compares favorably with a 24-hour urine collection for the diagnosis of proteinuria in women with suspected preeclampsia and has the advantage of convenience and improved clinical efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…This cut-off is associated with 99% specificity and 92% sensitivity for the diagnosis of pre-eclampsia. The use of the 12-hour urine collection would be more convenient, expedite diagnosis and clinical management, and decrease cost 33 . The results are awaited of the “diagnostic accuracy in pre-eclampsia using proteinuria assessment” (DAPPA) study, aimed at comparing the diagnostic accuracy of different methods of assessing proteinuria at various thresholds in predicting severe pre-eclampsia compared with 24-hour urine protein measurement 34 .…”
Section: New Developments In Predictionmentioning
confidence: 99%
“…This cut-off is associated with 99% specificity and 92% sensitivity for the diagnosis of pre-eclampsia. The use of the 12-hour urine collection would be more convenient, expedite diagnosis and clinical management, and decrease cost 33 . The results are awaited of the “diagnostic accuracy in pre-eclampsia using proteinuria assessment” (DAPPA) study, aimed at comparing the diagnostic accuracy of different methods of assessing proteinuria at various thresholds in predicting severe pre-eclampsia compared with 24-hour urine protein measurement 34 .…”
Section: New Developments In Predictionmentioning
confidence: 99%
“…The present study design followed the suggestions of Stout et al . by obtaining a large sample size, ensuring that the collection of urine was homogeneous, and stratifying the samples by diurnal versus nocturnal.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta‐analysis by Stout et al . found that 12‐hour urine collection, with a 150 mg cut‐off level for proteinuria, performed well among women with hypertension during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research quality assessment method follows a typical evidence-based procedure whereby experts are gathered, probe questions from a pool are chosen for a given diagnostic or screening question/tool, the questions' utility is field tested, and reliability of ratings is established. The QUADAS and QUADAS-2 are very widely used for both diagnostic and screening tests in both the behavioral [5254] and medical [5557] fields. This rating system was not applied formally (i.e., assigning numerical ratings) but instead adapted in the following way: (1) the four domains of Participants, Index Test (the screening tool), the Reference Standard (the “gold standard”), and Timing and Flow were used as units of review with the additional domains of Evaluation and Performance; (2) probe questions were developed for each of the domains; and (3) the probe questions were applied to each study and conclusions were summarized.…”
Section: Methodsmentioning
confidence: 99%